Prevalence And Risk Factors Of Gastrointestinal Helminths Among Ruminants In Veterinary Teaching Farm, Umk Bachok, Kelantan - Ding Tian Yang (2025)
An abstract of the research paper presented to the Faculty of Veterinary Medicine, Universiti Malaysia Kelantan, in partial requirement of the course DVT 55204 – Research Project. Gastrointestinal helminthiasis is a common infection in ruminants, leading to reduced productivity and increased disease susceptibility. A comprehensive screening of the entire herd has never been conducted although eggs of gastrointestinal parasites have been detected in some ruminant livestock at the Veterinary Teaching Farm, UMK Bachok. A cross-sectional study was conducted in October 2024 to investigate the prevalence, level of infection and risk factors of gastrointestinal parasitic infection among the ruminants in Veterinary Teaching Farm, UMK Bachok. Fecal samples were collected per rectum from cattle (n=16), buffaloes (n=1) and goats (n=16) in the farm. Gastrointestinal parasites were detected by performing the modified McMaster method, which serves the purpose of quantifying the strongyle eggs and oocysts per gram of faeces. The severity of infection was classified as low (0-500), moderate (501-2000), and severe (>2000). Fecal sedimentation was performed to detect the eggs of trematodes. Moreover, the identification and differentiation of infective stage larvae (L3) of the strongyles was carried out by performing fecal culture. Coprological examination reveals overall prevalence of 21.12% (CI = 0.641-22.744). Single infection with Eimeria (18.18%; CI =0.020-0.281) has the highest prevalence followed by strongyles (15.15%; CI =0.037-0.312). Coinfection with Fasciola spp. and Paramphistomum spp. recorded the lowest prevalence at 3.03% (CI = 0.114–0.421). Quantitative analysis revealed that 60% of strongyle infections were at a low level, while 40% were at a moderate level. The risk factors studied were not significantly associated with the prevalence of 5 gastrointestinal helminthiasis. The L3 of Haemonchus sp. and Trichostrongylus sp. were identified based on their morphology features. In conclusion, gastrointestinal parasites occur at low levels among ruminants in Veterinary Teaching Farm, UMK Bachok. Keywords: Gastrointestinal parasites, Fecal sedimentation, McMaster method